Pengaruh Faktor-Faktor Individual Terhadap Niat Melakukan Whistle-Blowing Internal Dan Eksternal Pada Akuntan Di Batam - Mega Mayasari; Adi Irawan Setiyanto; Rusda Irawati (Sekolah Vokasi Universitas Gadjah Mada, 2018)
This study aims to examine the perceptions of employees of the Accounting Section in Batam related with the influence of individual factors on the intention of conducting internal and external whistle-blowing. Intention is someone's desire to behave. The results of this study are expected to add understanding related to the perception of accounting employees to intentions of internal whistle-blowing and external whistle-blowing. The research team also hopes that the results of this research can be an input for companies in Batam, to design whistle blowing systems and report unethical acts at work, so as to detect fraud and ultimately good corporate governance can be created. The method used to obtain research data is through questionnaires distributed to employees of the Student Accounting Study Program of State Polytechnic of Batam who work as an accountant. The collected questionnaires were analyzed using PLS-SEM. The results of this study indicate that there is influence of whistle-blowing attitude toward intention to perform internal whistle-blowing, there is influence of subjective norm to intention to conduct external whistle-blowing, there is influence of perception behavior behavior to intention to do internal whistle-blowing. On the other hand, there is no effect of attitudes on whistle-blowing on intentions to external whistle-blowing, no subjective subjective effect on intent to conduct internal whistle-blowing, no influence of perceptual behavior control on intent to external whistle-blowing.